Evaluation of Judicial Institutions in Handling Contempt of Court Cases Based on Lawrence M. Friedman's Theory - Mohammad Reza Fachruddin; Abdul Muftar Rifki Maulana; Dewi Sulistianingsih; Martitah Martitah (Faculty of Law, Universitas Negeri Semarang, 2025)
This article examines the dynamics of the development of contempt of court using legal theory in the context of modern Indonesia by emphasizing the importance of a deep, open way of thinking, and involving various fields of knowledge. The author uses a qualitative method with a sociological approach, and refers to M. Lawrence Friedman's theory that sees law as part of social life with a case study of contempt of court. Legal understanding cannot be separated from social and political influences, the rigid theory of legal positivism is no longer adequate to answer the complexity of legal problems in Indonesian society. A transdisciplinary approach is offered as a conceptual solution to enrich legal theory through integration with social science, ethics, and legal philosophy. The results show that contempt of court requires the establishment of a separate law to strengthen legal legitimacy and public trust in the judiciary.